Media Pop-Up Book in Mirror Text Learning - Elsha Bella Pritiyana; Ariesty Fujiastuti (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Short story text is a type of writing that informs stories or stories about individuals and their intricacies through a short written content. The problem in this research is that the learning process is not optimal, namely the condition of students who are still less active in the learning process and students' reading interest is still low. This study aims to: develop pop-up book media for learning short story texts for junior high school students. This type of research uses the type of development (R&D) with the ADDIE development model. The trial subjects in this study were conducted by media experts, material experts, teaching experts and students in junior high schools as users of learning media. Data collection techniques and instruments used in this study were observation, interviews, and questionnaire sheets. Meanwhile, the data analysis technique used in this study was quantitative-descriptive data analysis.